Government intervention in chieftaincy matters in Ghana (Journal of Science and Technology, 2015)
Evidence in the form of oral tradition or recorded history is not wanting in demonstrating the fact that of all institutions in Ghana the most ancient as well as the most indigenous is the institution of chieftaincy. As such, it is shrouded in tradition otherwise called customary law and usage. The quest for progress in contemporary Ghana has however brought to light the pressing need for a purposeful shake-up in the institution through the instrumentality of law, with modernising overtones and undertones in order to save it from sinking into obsolescence and practical irrelevance, The burden of the present paper is to examine briefly how the Provisional National Defence Council (P.N.D.C.) government has been, and is, responding to the needed shake-up. In the process it will be argued that it is eminently desirable for the government to intervene, but otherwise for government to interfere, in chieftaincy matters.